PENGARUH RELASI INTERPERSONAL TERHADAP GAYA BELAJAR PENGURUS HIMA PRODI JURUSAN ILMU PENDIDIKAN FKIP UNIVERSITAS RIAU - Harahap, Nurintan Rahayu; Natuna, Daeng Ayub; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrak: This study aims to determine the effect of interpersonal relationships on the learning style of the HIMA PRODI management, Department of Education, FKIP, Riau University. The formulation of the problem in this study is whether there is a positive and significant influence on interpersonal relations on the learning style of the Hima Study Program management, Department of Education, FKIP, Riau University. This study consists of 2 variables, namely learning style (Y) and interpersonal relations (X), where the interpersonal relation variable consists of 4 indicators and the learning style variable (Y) has 3 indicators. The population in this study were the administrators of the HIMA PRODI Department of Education FKIP Riau University as many as 267 management. Sampling technique with simple random sampling. Simple random sampling is a method of selecting sample members from a population at random without regard to the strata that exist in the population. The data collection technique in this study was a questionnaire which consisted of 41 statements on the learning style variable (Y) and 39 statements on the interpersonal relation variable (Y). Based on descriptive analysis based on learning style variables, the mean value of 4.08 was obtained with a very good interpretation and descriptive analysis of the interpersonal relation variable (X) obtained a mean value of 4.25 with a very good interpretation. The Pearson correlation value obtained is 0.716 which indicates that there is a significant relationship between Interpersonal Relations (X) and Learning Styles (Y). The influence between interpersonal relations variables (X) and learning style (Y) is 51.30% while the remaining 48. 70% is determined by other factors that are not part of this study.Key Words: Interpersonal Relations, Learning Style, HIMA PRODI Management